Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1155/2020/1520747
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Curcumin on Aortic Atherosclerosis: A Systematic Review and Meta-Analysis in Mouse Studies and Insights into Possible Mechanisms

Abstract: Since the first report in 2005, accumulating interests have been focused on the effect of curcumin in atherosclerosis with discrepancies. Therefore, we conducted a systematic review and meta-analysis to comprehensively estimate its effect against atherosclerosis. Literature search was performed on the database of PubMed, EMBASE, and Cochrane Library to identify relevant studies which estimated the effect of curcumin in atherosclerosis. Reporting effects on aortic lesion area was the primary outcome while effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 61 publications
2
28
1
1
Order By: Relevance
“…In a recent meta-analysis that proposed to evaluate the therapeutic effect of curcumin in mouse models of atherosclerosis, Lin et al found that curcumin significantly decreases the aortic atherosclerotic lesion area, and the serum lipid levels (TC, TG and LDL-C) and inflammatory markers (TNF-α and IL-1β) [80]. In addition, Lin et al highlighted the dose-response relation between curcumin and its protective effect on atherosclerosis, showing that the effect on decreasing the aortic lesion area is stronger in low and medium dosages (< 207 mg/kg BW/day) and weaker when the dose was more than 207 mg/kg BW/day, becoming pro-atherogenic when the dose reached 347 mg/kg BW/day [80].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent meta-analysis that proposed to evaluate the therapeutic effect of curcumin in mouse models of atherosclerosis, Lin et al found that curcumin significantly decreases the aortic atherosclerotic lesion area, and the serum lipid levels (TC, TG and LDL-C) and inflammatory markers (TNF-α and IL-1β) [80]. In addition, Lin et al highlighted the dose-response relation between curcumin and its protective effect on atherosclerosis, showing that the effect on decreasing the aortic lesion area is stronger in low and medium dosages (< 207 mg/kg BW/day) and weaker when the dose was more than 207 mg/kg BW/day, becoming pro-atherogenic when the dose reached 347 mg/kg BW/day [80].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent meta-analysis that proposed to evaluate the therapeutic effect of curcumin in mouse models of atherosclerosis, Lin et al found that curcumin significantly decreases the aortic atherosclerotic lesion area, and the serum lipid levels (TC, TG and LDL-C) and inflammatory markers (TNF-α and IL-1β) [80]. In addition, Lin et al highlighted the dose-response relation between curcumin and its protective effect on atherosclerosis, showing that the effect on decreasing the aortic lesion area is stronger in low and medium dosages (< 207 mg/kg BW/day) and weaker when the dose was more than 207 mg/kg BW/day, becoming pro-atherogenic when the dose reached 347 mg/kg BW/day [80]. Clinical trials focusing on curcumin effects in atherosclerosis progression gave dissimilar results, some of them evidencing that curcumin has no effect on risk factors of atherosclerosis [81,82], while others reporting an atheroprotective effect of curcumin by improvement of the lipidic profile in patients with metabolic syndrome, patients taking curcumin extract capsules (630 mg thrice daily) for 12 weeks [83].…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin is a polyphenolic compound found primarily in the rhizomes of the ginger plant, and is believed to be one of the most biologically active natural products. It has been shown that curcumin has pharmacological effects in a wide variety of chronic diseases ( 18 , 19 ). Dong et al ( 20 ) speculated that curcumin or food rich in curcumin, have the potential to be a novel therapy for decreasing the risk of AS by increasing the expression levels of ABCA1 and increasing the cholesterol efflux in mouse adipocytes by the peroxisome proliferator activated receptor γ/liver X receptor α signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Lin et al ( 18 ) found that curcumin can inhibit ox-ldl-induced MCP-1 expression of VSMCs via the mitogen activated protein kinases (MAPK) and nuclear transcription factor κB (NF-κB) signaling pathway. Although a number of studies investigated the mechanisms behind the pharmacological activity of curcumin ( 18-20 ), the exact mechanism behind its pharmacological effects still remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Sirt3 located mainly in mitochondria regulates metabolism and oxidative stress [48,49]. The clinical drug metformin [22] and a number of natural bioactive compounds [52][53][54] have been reported to have anti-atherosclerotic effect, including curcumin, quercetin, puerarin, resveratrol, etc. by activating Sirt1 and/or AMPK.…”
Section: Discussionmentioning
confidence: 99%